Simulating method for TCP aggregated traffic of large scale network - CHEN Yu-feng1; DONG Ya-bo1; LU Dong-ming1; PAN Yun-he1 (Tongxin xuebao)
To obtain a trade-off between veracity and complexity when simulating TCP traffic of large-scale network,the TCP aggregated traffic of access network in the gateway was proposed as simulated object,instead of the traffic generated at the individual host or session level.Based on the self-similarity of application-level and network-level,the TCP aggregated traffic model was proposed due to the self-similarity of network traffic.The self-similar traffic at application level was generated by aggregating many ON/OFF sources following Pareto distribution.The aggregated transmission control was put on the traffic at network transmission level based on the mechanism of TCP protocol.Compared with the real data collected from a Network Exchange Center,the simulating result shows the validity of the model from the criteria of traffic load proportion,traffic self-similarity,and the packet loss ratio.